Comparison of ultrasound-guided closed reduction and percutaneous pinning fixation for unstable humeral lateral condylar fractures - Xu, Jianbing; Liu, Chaoyu; Jia, Guoqiang; Huang, Xiuming (Frontiers in Surgery, 2024)
Objective: Ultrasound-guided techniques have become popular in severe humeral lateral condylar fractures (HLCFs). This study compared the results of ultrasound-guided closed reduction and percutaneous pinning (UG-CRPP) for Song types 4 and 5 and dislocation type of HLCFs.Methods: This retrospective study was conducted in patients with HLCFs treated between January 2021 and October 2022 at three hospitals. The patients were divided into three groups according to Song's classification and elbow dislocation. The surgical time, reduction failure rate, and outcomes of the three groups were compared.The mean surgical time of the 94 patients across the three groups (Song 4 group, 42 cases; Song 5 group, 38 cases; and dislocation group, 14 cases) was the longest for Song 4 (66.14±23.05 min), followed by the dislocation group (59.71±21.07 min) and Song 5 (52.16±14.94 min) (for all, P=0.009). The failure rate decreased in the following order: dislocation group (5/14), Song 4 group (7/42), and Song 5 group (2/38). The failure rate of closed reduction in Song 4 was 3.2-fold higher than that in Song 5, and for the dislocation group, it was 7.6-fold higher than that in Song 5. Significant differences were observed between the Song 4, Song 5, and dislocation groups in terms of shaft-condylar angle and supination (P=0.015, P=0.043). No significant differences (P>0.05) were observed in the carry angle, flexion, extension, or pronation of the three groups. Two cases of delayed healing, four cases of superficial infection, one case of trochlear necrosis, and 39 cases of lateral spur in the Song 4 group were observed. In the Song 5 group, five had a superficial infection, one had re-displacement, and 26 had a lateral spur. In the dislocation group, there were two cases of superficial infection and 10 of lateral spurs.Conclusions: Song 4 HLCFs require longer surgical time and present more postoperative complications than Song 5 and dislocation-type HLCFs and can easily lead to lateral spurs. The failure rates of closed reduction in Song 4 and the dislocation type were higher than those in Song 5. Thus, UG-CRPP can be used to treat patients with unstable HLCFs.